Big insulin-like growth factor 2-producing multiple solitary fibrous tumors treated with debulking surgery: A case report - Keidai, Yamato; Murakami, Takaaki; Yamamura, Nana; Tsunoda, Shigeru; Ikeda, Atsushi; Hida, Koya; Nagao, Mototsugu; Yamada, Yosuke; Fukui, Ayaka; Ogura, Masahito; Fukuda, Izumi; Nakamoto, Yuji; et al. (Frontiers in Endocrinology, 2023)
Background: Non-islet cell tumor hypoglycemia (NICTH) is a rare paraneoplastic syndrome caused by a tumor-producing high molecular weight form of insulin-like growth factor 2 (IGF2) known as big IGF2. The only curative treatment for this condition is surgical resection of the responsible tumors. However, this may not be feasible in cases with multiple metastases at diagnosis of NICTH, and no standard treatment strategy for multiple tumors has been established. The effects of pharmacological therapies including somatostatin analogs are often inefficient and remain difficult to predict. Case Description: A 68-year-old man was admitted to our hospital due to impaired consciousness and severe hypoglycemia. His medical history included diagnosis of a left temporal solitary fibrous tumor (SFT) at the age of 48 years, after which local recurrent and metastatic tumors were repeatedly resected. Four years before admission, multiple intraabdominal and subcutaneous tumors were detected and, being asymptomatic, were managed conservatively. Laboratory exam on admission demonstrated hypoglycemia accompanied with low serum insulin and IGF1 levels. Computed tomography (CT) scan revealed multiple intraabdominal and subcutaneous tumors increasing in size. Serum big IGF2 was detected on immunoblot analysis, and he was diagnosed as NICTH. In addition, tumor uptake was observed on 68Ga-labelled 1,4,7,10-tetraazacyclododecane-N,N’,N’’,N’’’-tetraacetic acid-d-Phe1-Tyr3-octreotide positron emission tomography/CT (DOTATOC-PET/CT). Since larger tumor is more suspicious about responsible producibility of big IGF2, we planned to resect large ones preferentially and reduce the amounts of residual tumors. Debulking surgery was performed by removing eleven intraabdominal tumors; the hypoglycemia was then completely corrected. Histological analyses revealed the resected tumors to be metastases of SFT having somatostatin receptor 2 expression. In immunoblot analysis, the resected tumors were found to be positive for big IGF2; serum big IGF2 was undetectable after surgery. Conclusion: We present a case of NICTH with multiple metastatic SFTs. We strategically performed debulking surgery, which led to remission of hypoglycemia. In addition, in cases of SFTs presenting with NICTH, positivity of DOTATOC-PET/CT as well as single-dose administration of octreotide may be predictive of the efficacy of somatostatin-based therapy.